2021
DOI: 10.1016/j.afjem.2021.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Reaching further: Lessons from the implementation of the WHO Basic Emergency Care Course Companion App in Tanzania

Abstract: Introduction The World Health Organization's (WHO's) Basic Emergency Care (BEC) course was developed to address training gaps in low- and middle-income countries (LMICs). Simultaneously, LMICs have experienced an unprecedented increase in the number of cell phone and internet users. We developed a mobile application adjunct to the BEC course (BEC app) and sought to assess the reach of the BEC app. Methods Forty-six BEC course participants, made up of doctors and nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In research, for example, the Basic Emergency Care course application was developed and applied in Tanzania. The researchers reported limitations in Internet access; however, they found potential utility [10]. Hence, the research team considered that the use of an educational app is possible, especially among professional groups with economic stability.…”
Section: Introductionmentioning
confidence: 99%
“…In research, for example, the Basic Emergency Care course application was developed and applied in Tanzania. The researchers reported limitations in Internet access; however, they found potential utility [10]. Hence, the research team considered that the use of an educational app is possible, especially among professional groups with economic stability.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, FG responses suggested that the BEC app was user-friendly, clear and easy to navigate and a helpful resource in retaining information from BEC course. However, a number of challenges identified both by moderators during the implementation of the BEC app 20 and by participants during the FGs discussions may have limited the impact of the BEC app, resulting in the negative findings of this study.…”
Section: Discussionmentioning
confidence: 87%
“…This level of resource may not be feasible for mass distribution of such an intervention and barriers to access may be even greater than reported here. However, this enabled a comprehensive understanding of implementation challenges, 20 which can be used to further refine the intervention and its roll-out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the pilot BEC programs in Zambia, Tanzania, and Uganda, additional iterations have been implemented in emergency facilities in Nigeria, Sierra Leone, Ukraine, and Kiribati and adapted for each clinical context [30][31][32][33]. In these cases, knowledge acquisition was similarly measured by comparing pre-and post-course assessments.…”
Section: Plos Onementioning
confidence: 99%